Development of magnesium phosphate cement rapid reapir mortar - Monsan Visesgahamin; Pennung Warnitchai; Sun Sayamipuk; Thanakorn Pheeraphan; RTG Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
A study was focused on investigating the properties of Magnesium Phosphate Cements (MPCs) and optimizing the mix proportion of Magnesium Phosphate Cement. The pozzolans namely fly ash and metakaolin have been selected as constituents to improve the quality of Magnesium Phosphate Cements. The magnesium and phosphate were used in the amount of 10 percents to 30 percents by weight of cement whereas the percentage replacement of fly ash and metakaolin were varied from 10 percents to 30 percents by weight of cement, respectively. The water to binder ratio (W/B) of the mixtures was fixed at 0.45. For the first phase, the optimization mix proportion which gained the highest compressive strength at the age of 24 hours and 72 hours was used as the main constitute for all MPCs mixes in the second phase. For the second phase, the physical and mechanical properties such as the setting time, bonding strength, flexural strength, and compressive strength at age 6 hours, 24 hours, 72 hours, 168 hours, 672 hours and 2,184 hours were determined. For phase I, it was found that the optimum mix proportion of the MPCs mortar composed of sand/binder (s/b) ratio of 2.0 and binder which was 90 percents of Ordinary Portland Cement, 5 percents of Magnesium and 5 percents of phosphate. When the fly ash and metakaolin were replaced Ordinary Portland cement, the results indicated that the use of fly ash replacement in MPCs mortars extended the initial and final setting times, but led to reduction of compressive strength, flexural strength and bonding strength. Whereas the MPCs mortar containing metakaolin can increase the compressive strength, flexural strength, bonding strength, but the setting time was decreased. Hence, the metakaolin can be used as cement replacement in MPCs cement and enhanced the performance for making the repaired cement mortar.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 2010
Keywords: Concrete; Mortar